Murray & Nadel's textbook of respiratory medicine - Broaddus, V. Courtney; Mason, Robert J. (Elsevier Saunders, 2016)
Ideal for fellows and practicing pulmonologists who need an authoritative, comprehensive reference on all aspects of pulmonary medicine, Murray and Nadel's Textbook of Respiratory Medicine offers the most definitive content on basic science, diagnosis, evaluation and treatment of the full spectrum of respiratory diseases.